Creating Pembuatan Roster Daur Ulang Sampah Plastik untuk Peningkatan Ekonomi di Kelurahan Margaluyu (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2026)
This community service was carried out in Margaluyu Village, Kasemen District, Serang City. This community service program was prepared based on the problem of increasing the amount of household plastic waste in Margaluyu Village which until now has not been managed optimally. As an innovative effort in handling this problem, the community service team held a training activity on making wind hole breeze breeze blocks using mixed materials in the form of shredded plastic and silica sand. This community service program not only focuses on efforts to reduce the level of environmental pollution, but also directs inorganic waste to be processed into building materials that have aesthetic value as well as high benefits for local residents. The activity was carried out with a focus on strengthening the role of youth groups and fathers as the main drivers of the creative economy at the village level. In the demonstration session, participants were invited to directly practice steps ranging from plastic sorting, the enumeration process, to roster printing techniques that require high precision. In addition, the team also provided technical assistance and simulations of production cost calculations so that participants understood the potential economic value of the product. Participatory discussions were conducted to explore field challenges, while the final evaluation showed an improvement in the participants' skills and environmental awareness.